Learning Theories and Teaching Methodologies for the Design of Training in Digital Competence for Language Teachers: A Narrative Review - Parmaxi, Antigoni; Nicolaou, Anna; Kakouli-Constantinou, Elis; Soule, Maria Victoria; Papadima-Sophocleous, Salomi; Perifanou, Maria (My University, 2021)
This paper provides a narrative review of learning theories and teaching methodologies that can be used to design training activities for an online or blended training workshop addressed to language teachers. The review was performed in a traditional, narrative manner and revolved around the exploration of recent, influential learning theories, such as Connectivism, Social Constructionism, and Ecological Theory. It also involved an exploration of contemporary teaching methodologies, such as game-based learning, problem-based learning, and virtual exchange, which were deemed important for language teachers in order to get an up-to-date overview of theoretical perspectives and improve their teaching. This review is part of the Digital Competence for Language Teachers (DC4LT) Erasmus+ KA2 project and its ultimate objective was to delineate an array of learning theories and teaching methodologies in order to enable trainers to select the ones that are most suitable for training workshops in digital competence for language teachers. The specific review concludes with implications for the design of a training workshop with replicability and transferability potential for future trainers.
Keywords: Digital competence; Language instruction; Learning theories; Teaching methodologies